2021
DOI: 10.5334/cstp.370
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Motivations of Environmental Citizen Scientists

Abstract: Understanding motivations is important because appealing to and fulfilling motivations helps citizen science projects recruit and retain participants. We summarise the literature around motivations, drawing on key theories from volunteering more broadly and building on this with additional motivations identified in studies of citizen scientists. We also examine what is known about differences in motivations between demographic groups. We then report on a survey of 613 environmental citizen scientists in Great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 47 publications
(83 reference statements)
4
59
0
Order By: Relevance
“…A citizen-driven approach also requires considerations that span beyond data-collection design and implementation. First, participant motivation is key to ensuring sustainable, long-term participant engagement (Pocock et al 2019;Ashepet et al 2021;West et al 2021). Second, Pocock et al (2019) identified the reluctance of uptake of citizen science by policy makers as an important institutional barrier for their implementation in East Africa.…”
Section: Beyond the Pilot Study: Broader Perspectives For Citizen Science And Vector Monitoring In Resource-limited Settingsmentioning
confidence: 99%
“…A citizen-driven approach also requires considerations that span beyond data-collection design and implementation. First, participant motivation is key to ensuring sustainable, long-term participant engagement (Pocock et al 2019;Ashepet et al 2021;West et al 2021). Second, Pocock et al (2019) identified the reluctance of uptake of citizen science by policy makers as an important institutional barrier for their implementation in East Africa.…”
Section: Beyond the Pilot Study: Broader Perspectives For Citizen Science And Vector Monitoring In Resource-limited Settingsmentioning
confidence: 99%
“… 2021 , West et al. 2021 ). For example, assessing engagement in citizen science supported by intermediaries or facilitators (e.g., schools, Scout groups, or corporate volunteer programs) might reveal new insights into barriers to broadening participation (Salmon et al.…”
Section: Key Findings Regarding Multiproject Participationmentioning
confidence: 99%
“…The focus should not be on data contribution only, instead, the core principles 'learning by doing' and 'being part of a community' should be communicated. Learning something new is one of the major motivations for citizen science participants (West et al, 2021) and these principles are regarded as an important basis in the design process of educational citizen science projects even though more research is needed concerning the design and use of tools (Herodotou et al, 2018).…”
Section: / 12mentioning
confidence: 99%